Optimizing aged care environments to promote resident functional mobility and reduce staff injury risk - Coman, Robyn; Caponecchia, Carlo (Frontiers in Aging, 2023)
Abstract Introduction: This study aimed to evaluate the suitability and usability of the Pro-Mobility patient/person handling assessment tool (ProMob) within residential aged care. Physiological changes associated with ageing influence an older person’s ability to perform functional mobility tasks such as transferring from furniture and walking. Strategies that improve capability and/or reduce the physical demands of the task have the potential to promote an older person’s mobility, independence and wellbeing. Environment-related strategies in Manual Handling of People (MHP), such as optimum seated heights, in part address this challenge, as they can promote resident functional mobility while also protecting staff from injury. The ProMob tool was developed to address this issue through systematic evaluation of these environmental factors. Methods: The participants in this study were seven (7) residential aged care facilities (RACFs) operated by a not-for-profit aged care organization. A qualified assessor evaluated MHP risk management with the ProMob tool at each RACF through collection of data for a random sample of residents (n=67) regarding their living environments and available mobility information. Data was transferred to an SPSS-22 statistical software database for analysis which involved descriptive statistics and cross tabulations. Results: Application of the ProMob tool provided effective quantification of the nature and extent of environment-related MHP interventions that may influence resident mobility. Areas for improvement with MHP risk management were identified, with variation evident across RACF’s within the same organisation, which was not consistent with levels of care (e.g. lack of clear space to facilitate mobility). Low level care facilities were observed to have fewer adaptive environmental features that could potentially slow decline in independence. Discussion: Features of the aged care environment can be used to facilitate the functional mobility of aged care residents, and simultaneously reduce injury risk for staff in MHP interactions. The ProMob tool can be used for auditing care facilities, planning re-development, and continual improvement in provision of care and management of staff injury risk exposure.